Decoding scent-marking behavior of Asiatic lions in Gir Forest, Gujarat, India - Ram, Mohan; Sahu, Aradhana; Srivastava, Nityanand; Mahajan, Prashant; Baraiya, Sneha; Dagur, Tanisha; Jhala, Lahar (Frontiers in Ecology and Evolution, 2025)
This study provides novel insights into the scent-marking behaviors of free-ranging Asiatic lions (Panthera leo persica) in the dry deciduous forests of Western India, focusing on spatial and temporal patterns as well as the factors influencing the selection of scent-marking sites. Using camera traps, we identified that scent-marking and associated behaviors are predominantly exhibited during crepuscular and nocturnal hours, with peaks at dawn and dusk. Seasonal variation was observed, with increased activity during winter, coinciding with the breeding period. Sniffling was the most frequent behavior observed, followed by scratching and spraying. Adult males were more engaged in these behaviors than females, likely due to territorial defense and reproductive strategies. Our analysis of tree characteristics revealed a preference for trees near forest tracks or trails, especially those with rough bark and aromatic properties, which may enhance the persistence and detection of scent marks. This study is the first comprehensive analysis of scent-marking behaviors in Asiatic lions. It lays the foundation for future research into individual scent-marking patterns using GPS-collaring and camera traps. Understanding these behaviors is important for the better conservation of this endangered species.